The Impact of the Brainrot Phenomenon on the Concentration of Year 8 Students at MTs Negeri 3 Bogor - Najwatu Sholihah; Elis Lisyawati (Yayasan Rahmat Islamiyah, 2026)
This study aims to investigate the impact of the brainrot phenomenon on students’ concentration during learning, specifically among Year 8 students at MTs Negeri 3 Bogor. This study employs a quantitative approach using a survey method. The study population consists of 348 students, with a sample of 186 students selected via random sampling. Data were collected via a questionnaire that had been tested for validity and reliability. The data were analysed using prerequisite tests, namely normality and linearity tests, as well as simple linear regression analysis using SPSS software. The results of the study indicate that the brainrot phenomenon has a negative effect on students’ concentration during learning, with a significance level (Sig.) of 0.001 and a regression coefficient of -0.137. The coefficient of determination indicates that the brainrot phenomenon contributes 6.8% to students’ concentration during learning, whilst the remaining 93.2% is attributed to other factors outside the scope of this study. Nevertheless, the results of this study still indicate that excessive exposure to instant digital content without proper time management can reduce students’ ability to concentrate during learning activities. Therefore, wise and strategic management of digital media, along with more thorough lesson planning, is required as a strategy to maintain students’ focus and engagement in today’s digital age.